Pengaruh Gender, Tipe Kepribadian, Tingkat Pendidikan, dan Pengalaman Audit Terhadap Skeptisme Auditor Internal Pemerintah (Studi Empiris pada Inspektorat Provinsi Jawa Timur) - Jannah, Fairuz; Pratono, Rudi (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
The purpose of this study is to determine the effect of gender, personality type, audit experience and auditor education level on the skepticism of the internal auditor of the government. The number of samples used in this study were 50 respondents taken by accidental sampling method, namely sampling based on convenience and being in the right situation, time and place. Data analysis in this study uses multiple linear regression with the help of SPSS version 17.0. this shows that gender, personality type, audit experience, and auditor education level significantly influence the skepticism of the internal auditors of the government